1975
DOI: 10.1073/pnas.72.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant DNA molecules of bacteriophage phi chi174.

Abstract: ABSTRACT4 X174 DNA structures containing two different parental genomes were detected genetically and examined by electron microscopy. These structures consisted of two monomeric double-stranded DNA molecules linked in a figure 8 configuration. Such DNA structures were observed to be formed preferentially in host recA+ cells or recA + cell-free systems. Since the host recA + allele is required for most 4OX174 recombinant formation, we conclude that the observed figure 8 molecules are intermediates in, or end p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…One of them, the DNA exchange model [3], was proposed at the time when it first seemed clear that circular DNA molecules were intermediates in the formation of proviral DNA. This, and an awareness of the discontinuity of the positive strands, made plausible a type of exchange that had been suggested earlier for the circular DNA of bacteriophage 4x174 [23]. It can be seen that this model is similar in concept, though different in detail, to the displacement/ assimilation model.…”
Section: Comparison With Other Models For Retroviral Recombinationsupporting
confidence: 61%
“…One of them, the DNA exchange model [3], was proposed at the time when it first seemed clear that circular DNA molecules were intermediates in the formation of proviral DNA. This, and an awareness of the discontinuity of the positive strands, made plausible a type of exchange that had been suggested earlier for the circular DNA of bacteriophage 4x174 [23]. It can be seen that this model is similar in concept, though different in detail, to the displacement/ assimilation model.…”
Section: Comparison With Other Models For Retroviral Recombinationsupporting
confidence: 61%
“…We were led to do these experiments by speculations about the initiation of general genetic recombination (1,24). According to one version of such speculations, an early event in recombination is the uptake by a recipient double-stranded molecule of a redundant strand displaced from a homologous donor.…”
Section: Discussionmentioning
confidence: 99%
“…This process, involving transfer of homologous regions of DNA, depends upon the annealing of complementary strands to produce, at an early stage in recombination, a region of duplex DNA containing one strand from each parental DNA molecule (3,4). Numerous studies have suggested that such heteroduplex overlaps are not formed in recA mutants, in contrast to other recombination-deficient mutants (e.g., recB, recC) (5)(6)(7)(8)(9)(10). Thus, although a number of genes can affect recombination, only the recA function has been implicated in strand transfer.…”
mentioning
confidence: 99%